Gadai Emas Alternatif Tambahan Modal Usaha Mikro Kecil dan Menengah Pada Lembaga Keuangan Syariah - Ninda Ardiani; Muhammad Nafik HR (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The method used is a qualitative approach with the strategy case study. The collection of data that is passed is the interview to the informant, the assistant pawn Islamic financial institutions and Micro, Small and Medium Enterprises customers pawn gold. The analysis technique used is the technique of pairing patterns with narrating the interviews with informants. Results from this study is the gold pawn Islamic financial institutions may be a reinforcement of capital Micro, Small and Medium Enterprises. The use of gold as a pledge of capital strengthening of capital Micro, Small and Medium Enterprises undertaken to meet short-term capital in the form of working capital. Requirements are simple and fast process makes this product desirable pengusha Micro, Small and Medium Enterprises. Using gold as a pledge of additional capital, the of capital Micro, Small and Medium Enterprises business grew and developing States.